Tumor fibroso calcificante intestinal: reporte de caso - Cantú-Soriano, Gonzalo Nathaniel; Padilla Rodríguez, Álvaro Lezid (Elsevier, 2023)
Calcifying fibrous tumor (CFT) is a rare benign lesion of mesenchymal origin that may present similar characteristics to other more common tumors. We present the case of a 36-year-old woman with a tumor in the proximal jejunum, initially suspected to be a gastrointestinal stromal tumor (GIST). Surgical resection was performed, revealing a well-demarcated nodule at the anti-mesenteric border with microscopic features typical of a calcifying fibrous tumor. The tumor cells were positive for CD34 and negative for other markers, differentiating it from other neoplasms. Calcifying fibrous tumors can be confused with more common tumors because of its appearance, but an accurate diagnosis supported by immunohistochemistry is essential. Complete surgical excision is usually curative. © 2023 Sociedad Española de Anatomía Patológica. ©Elsevier
Intestinal calcifying fibrous tumor: case report
Keywords: Calcifying fibrous tumor; Heterotopic pancreatic tissue; Immunohistochemistry; Mesenchymal neoplasm